The Radon Gas in Underground Constructions. Railway Tunnel of Alicante (Spain) - Rizo Maestre, Carlos; ChinchÃ³n Yepes, Servando; Echarri Iribarren, Victor (International Journal of Engineering and Technology, 2018)
The presence of radon gas in constructions is an indicator of air quality. The study presented analyzes the amount of radon gas in the Railway Tunnel in Alicante. This infrastructure is very important for the city due to its social importance in facilitating urban mobility. radon gas is an element considered highly harmful to people by different scientific agencies in the field of medicine and health, including the World Health Organization (WHO). The main effect of the presence of radon in the environment of the human being is the risk of contracting lung cancer. This radioactive gaseous element is present in almost all building materials, and in the land in which the buildings are implanted. In this article the measurements made in the tunnel are provided and the levels obtained are analyzed according to their danger to humans. In Spain, the Technical Building Code (CTE) still does not contemplate the dose of radon that can hold a maximum of one building and how to contain it.Â Â